Junius. - (:unkn) unknown (My University, 1785)
Scholarly notes may be added at a later date.
1 print : b&w
Keywords: Caricatures; Cartoons; Burke, Edmund, 1729-1797. A Philosophical Enquiry into the Origin of our Ideas of the Sublime and Beautiful; Junius, 18th cent.